واقع مساىمة القطاعات الإنتاجية في تحقيق التنويع الاقتصادي ودورىا في الخروج من صفة الاقتصاد الأحادي - - في الجزائر دراسة تحليلية للفترة 2020 2000: The Reality of the Contribution of the Productive Sectors to Achieving Economic Diversification and their Role in Abandoning the Monolithic Economy in Algeria - An Analytical Study of the Period 2000-2020 - محمد دعمي (Journal of North African Economies, 2025)
This research paper aims to show the reality of the productive sectors’ contribution to achieving economic diversification during the period 2000 and 2020 and their role in abandoning the monolithic economy by studying economic diversification indicators on one hand, and using the Herfindahl-Hirschman index to measure the degree of economic diversification on the other. We relied on official statistical data from various government agencies to conclude that the Algerian Economy is monolithic. We found very few and weak indications in some secondary indicators of the trend towards economic diversification, particularly between 2015 and 2002. In this context, Algeria can apply a set of means and mechanisms linked to all productive sectors to achieve full economic diversification.